Jahresbericht des Vereins Kunsthalle Bern 1979 / 1980. - Gachnang, Johannes; Kunsthalle Bern (Bern : Kunsthalle Bern, 1980)
Kirkeby, Per ; Zaugg, Rémy ; Chamberlain, John ; Fabro ; Kounellis ; Merz ; Paolini
Engels
boek